Implementasi Strategi Fungsional Bagi Keberhasilan Penerapan Corporate Strategy pada PT. BPR Syariah di Jawa Timur - Rofiaty, Rofiaty (TEMA, 2005)
The study applies the resources-based strategy of firm, which focuses on the effect offunctional strategy for the effectiveness of corporate strategy application. The two main purpose of this study were : (1) to discover the simultaneous and partial relationship of variables the functional strategy (operational, financial, marketing and human resources) for the effectiveness of corporate strategy application., and (2) to determine variable which has the biggest influence on the effectiveness of corporate strategy application. The result of this research shows that (1) positive significant influence is the evidence of functional starategy (4 variable) for the effectiveness of corporate strategy application. (2) marketing variable has the biggest influence on effectiveness of corporate strategy applications.Keyword: implementation strategy, corporate strategy, functional strategy